2013
DOI: 10.1371/journal.pone.0080583
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Variation of Human Papillomavirus Type 16 in Individual Clinical Specimens Revealed by Deep Sequencing

Abstract: Viral genetic diversity within infected cells or tissues, called viral quasispecies, has been mostly studied for RNA viruses, but has also been described among DNA viruses, including human papillomavirus type 16 (HPV16) present in cervical precancerous lesions. However, the extent of HPV genetic variation in cervical specimens, and its involvement in HPV-induced carcinogenesis, remains unclear. Here, we employ deep sequencing to comprehensively analyze genetic variation in the HPV16 genome isolated from indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 48 publications
(55 reference statements)
1
37
0
1
Order By: Relevance
“…Although it was difficult to detect a small population of variants in the host genome using a traditional approach such as PCR, NGS, owing to its depth, enabled us to detect a novel genomic variation (27). NGS has strongly supported the studies of viral genetic diversity, especially in RNA viruses (28,29), whereas the detection by NGS of quasispecies in DNA virus has been reported less frequently (30)(31)(32)(33). Using PCR analysis, the presence of VP1 quasispecies has been reported in polyomavirus BK (BKV) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was difficult to detect a small population of variants in the host genome using a traditional approach such as PCR, NGS, owing to its depth, enabled us to detect a novel genomic variation (27). NGS has strongly supported the studies of viral genetic diversity, especially in RNA viruses (28,29), whereas the detection by NGS of quasispecies in DNA virus has been reported less frequently (30)(31)(32)(33). Using PCR analysis, the presence of VP1 quasispecies has been reported in polyomavirus BK (BKV) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Studies that analyzed the near full HPV16 genome, using deep sequencing, did not observe any deletion event in the invasive cervical cancer samples analyzed [39,48]. However, a significant increase in read depth close to L1 and L2, respectively, compatible with a duplication event of a genome fragment spanning these regions was observed [39].…”
Section: Hpv Diversity and Cancermentioning
confidence: 99%
“…Intrahost next-generation sequencing data have shown that HPV16 episomes present in the W12 cell line did not accumulate sequence variation above 0.5% [48]. However, the same authors reported that more than 40% of the clinical samples contained polymorphic sites reaching frequencies up to 5% [48].…”
Section: Hpv Diversity and Cancermentioning
confidence: 99%
“…To comprehensively explore the quasispecies status of the HPV16 genome in individual clinical specimens, the mutational landscape in the full-length HPV16 genome was investigated with NGS technology (36). In that study, whole HPV16 genomes were amplified with onestep, long-range PCR from HPV16-positive clinical samples of either CIN1 or ICC, and analyzed by deep sequencing.…”
Section: Quasispeciesmentioning
confidence: 99%
“…The physiological relevance of HPV16 hypermutation in the viral life cycle and cervical carcinogenesis has yet to be determined, because hypermutation in E2 and the LCR in clinical samples seems to be extremely rare in total viral populations, insofar as deep sequencing analysis was unable to detect hypermutated HPV16 sequences at frequencies of more than 0.5z (36). One intriguing possibility is that hypermutation is involved in the integration of HPV into the host genome, a critical event in the generation of cervical cancer, because E2 is a``hot spot'' for HPV integration and is frequently disrupted by integration (50).…”
mentioning
confidence: 99%